Technological capabilities, technological dynamism and innovation offshoring - Torben Schubert; Elisabeth Baier; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
In this paper we analyze the conditions under which firms decide to offshore innovation. We consider the role of internal technological capabilities and technological dynamism in the firm environment, distinguishing speed and uncertainty of technological change. Using unique data from the German Innovation Survey we find that while high speed of technological change tends to drive innovation offshoring, high uncertainty about future technology developments results in more innovation offshoring only for firms with low internal technological capabilities. Firms with high technological capabilities instead are less likely to offshore innovation when uncertainty is high. We argue that these differences in offshoring behaviour reflect differing strategic objectives. We show that for firms with low technological capabilities asset augmentation is more important while for firms with high technological capabilities asset exploitation is more important. When faced by high technological uncertainty firms with low technological capabilities offshore innovation strategically in order to reduce uncertainty by augmenting their asset base. For firms with high technological capabilities asset augmentation is less important. When faced by high technological uncertainty they prefer to innovate onshore in order to keep stronger control of their key assets.
urn:nbn:de:bsz:180-madoc-412315
Keywords: O32; F21; F23; L22; 330